Cross-border Cooperation in Barents Tourism: Insights from Finnish Lapland - Koskinen, Mira (Rovaniemen ammattikorkeakoulu, 2013)
The main aim of this thesis project was to obtain a better understanding of how the tourism industry in the Barents Region could be developed through multilateral cross-border cooperation. The main focus was on discovering the needs and expectations that the tourism practitioners in Finnish Lapland have. Furthermore, the thesis gives an introduction to the prevailing conditions in the Barents Region and connects them to the historical and political frameworks affecting the current matters. The theoretical underpinning of the cross-border cooperation phenomenon is introduced in a general level with paying particular attention to the European context. Moreover, as to uncover the prospective benefits and challenges of cross-border tourism cooperation, a review on the respective literature was conducted consequently supplying some critical notions and suggestions for the tourism-specific cross-border activities. In order to uncover the needs and expectations of the tourism practitioners, an empirical research was conducted. The used research methods included semi-structured theme interviews and surveys with tourism practitioners operating in Finnish Lapland. The acquired data was categorized and both the interview and survey data were analysed using content analysis. Four data-driven focus themes were selected to address the issues, namely, forms of cooperation, knowledge and education, accessibility and facilitators. The research questions were formulated in accordance with the selected themes, including 1) Which forms of cooperation are of interest to the tourism practitioners? 2) What kind of knowledge and training is needed among the tourism practitioners? 3) Which issues related to accessibility should be tackled and enhanced in the Barents Region? and 4) Which actors are important for improving the cross-border tourism cooperation?. The empirical findings suggest that the tourism practitioners in Finnish Lapland are interested in cross-border tourism cooperation, especially in tourism product development and ...